2001
DOI: 10.1080/j.1600-0412.2001.801205.x
|View full text |Cite
|
Sign up to set email alerts
|

Four years experience of first-trimester nuchal translucency screening for fetal aneuploidies with increasing regional availability

Abstract: Background. A prospective screening study was carried out at the regional genetic and perinatal center in South Hungary in order to determine the efficiency of first-trimester nuchal translucency screening for fetal aneuploidies, following augmentation of the availability of nuchal translucency screening in the region by the inclusion of newly-trained hospital sonographers. Methods. Nuchal translucency thickness was measured by transvaginal sonography in 7,044 women with singleton or multiple pregnancies at we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…is similar to the results of the previous 14 prospective studies examining the implementation of fetal NT measurement in screening for chromosomal defects 2,[12][13][14][15][16][17][18][19][20][21][22][23][24] . Thus, the combined results on a total of 174 473 pregnancies, including 728 with trisomy 21, demonstrated a detection rate of 77% for a false-positive rate of 4.7%.…”
Section: Type Of Pregnancysupporting
confidence: 89%
“…is similar to the results of the previous 14 prospective studies examining the implementation of fetal NT measurement in screening for chromosomal defects 2,[12][13][14][15][16][17][18][19][20][21][22][23][24] . Thus, the combined results on a total of 174 473 pregnancies, including 728 with trisomy 21, demonstrated a detection rate of 77% for a false-positive rate of 4.7%.…”
Section: Type Of Pregnancysupporting
confidence: 89%
“…There are 14 prospective studies examining the implementation of nuchal translucency measurement in screening for chromosomal defects (Table 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Although different cut-offs were used for identifying the screenpositive group, with consequent differences in the false-positive rate and sensitivity, they all reported high detection rates.…”
Section: Screening For Trisomy 21mentioning
confidence: 99%
“…In the 1990s it was realized that this excess skin could be visualized by ultrasonography as increased NT in the third month of intrauterine life6. Fetal NT at the 11–14‐week scan has been combined with maternal age to provide an effective method of screening for trisomy 21; for an invasive testing rate of 5%, about 75% of trisomic pregnancies can be identified7–20. When maternal serum free‐β‐human chorionic gonadotropin (β‐hCG) and pregnancy‐associated plasma protein‐A (PAPP‐A) at 11–14 weeks are also taken into account, the detection rate of chromosomal defects is about 90%21–25.…”
Section: The 11–14‐week Scanmentioning
confidence: 99%
“…There are 14 prospective studies examining the implementation of NT measurement in screening for trisomy 21 (Table 4)7–20. Although different cut‐offs were used for identifying the screen‐positive group, with consequent differences in the false‐positive and detection rates, all the studies reported high detection rates.…”
Section: The 11–14‐week Scanmentioning
confidence: 99%